2020
DOI: 10.1097/md.0000000000021193
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity and specificity of statistical rules for diagnosing delayed neurocognitive recovery with Montreal cognitive assessment in elderly surgical patients

Abstract: Delayed neurocognitive recovery (DNR) is common in elderly patients after major noncardiac surgery. This study was designed to investigate the best statistical rule in diagnosing DNR with the Montreal cognitive assessment (MoCA) in elderly surgical patients. This was a cohort study. One hundred seventy-five elderly (60 years or over) patients who were scheduled to undergo major noncardiac surgery were enrolled. A battery of neuropsychological tests and the MoCA were employed to test cognitive functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Clinicians are expecting novel biomarkers, yet few studies could achieve long-term postoperative tracking and evaluation of patients, as well as observe the impact on cognition by perioperative biophilic VR intervention, we will apply the method of Montreal Cognitive Assessment (MoCA) test as recent study suggested that the 2 scores rule with MoCA had the best combination of sensitivity and specificity to diagnose delayed neurocognitive recovery. 15 A prospective, randomised, clinical trial is designed to assess the efficacy of biophilic VR to decrease the incidence of POCD and the severity of anxiety in patients undergoing laparoscopic surgery. We hypothesise that biophilic VR will be more effective at reducing anxiety and incidence of POCD in this population than a sham control.…”
Section: Why Biophilic Virtual Reality?mentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians are expecting novel biomarkers, yet few studies could achieve long-term postoperative tracking and evaluation of patients, as well as observe the impact on cognition by perioperative biophilic VR intervention, we will apply the method of Montreal Cognitive Assessment (MoCA) test as recent study suggested that the 2 scores rule with MoCA had the best combination of sensitivity and specificity to diagnose delayed neurocognitive recovery. 15 A prospective, randomised, clinical trial is designed to assess the efficacy of biophilic VR to decrease the incidence of POCD and the severity of anxiety in patients undergoing laparoscopic surgery. We hypothesise that biophilic VR will be more effective at reducing anxiety and incidence of POCD in this population than a sham control.…”
Section: Why Biophilic Virtual Reality?mentioning
confidence: 99%
“…Clinicians are expecting novel biomarkers, yet few studies could achieve long-term postoperative tracking and evaluation of patients, as well as observe the impact on cognition by perioperative biophilic VR intervention, we will apply the method of Montreal Cognitive Assessment (MoCA) test as recent study suggested that the 2 scores rule with MoCA had the best combination of sensitivity and specificity to diagnose delayed neurocognitive recovery. 15 …”
Section: Introductionmentioning
confidence: 99%